2009
DOI: 10.1051/radiopro/20095104
|View full text |Cite
|
Sign up to set email alerts
|

Findings and recommendations from an international comparison of models and approaches for the estimation of radiological exposure to non-human biota

Abstract: Abstract. There is general international acceptance of the need to demonstrate that the environment is protected from ionising radiation. In some countries requirements and guidelines for the protection of non-human biota are already in place. As a consequence a number of models and approaches have been proposed for the estimation of the exposure of non-human biota to ionising radiation. The IAEA EMRAS programme's Biota Working Group has conducted the most comprehensive intercomparison of the predictions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…In part, this is a consequence of the different organisms considered in the three models. It is also in agreement with other comparisons of models/approaches used to estimate exposure of biota which have demonstrated that the dosimetry components generally estimate comparable results [1][2][3]. The greater variability observed in estimated RQ values between models when assuming 1 Bq kg −1 in freshwater sediments may be the consequence of RESRAD-BIOTA using terrestrial soil-soil water k d values rather than freshwater sediment-water k d values [10].…”
Section: Variation In Estimated Rq Valuessupporting
confidence: 76%
See 2 more Smart Citations
“…In part, this is a consequence of the different organisms considered in the three models. It is also in agreement with other comparisons of models/approaches used to estimate exposure of biota which have demonstrated that the dosimetry components generally estimate comparable results [1][2][3]. The greater variability observed in estimated RQ values between models when assuming 1 Bq kg −1 in freshwater sediments may be the consequence of RESRAD-BIOTA using terrestrial soil-soil water k d values rather than freshwater sediment-water k d values [10].…”
Section: Variation In Estimated Rq Valuessupporting
confidence: 76%
“…The large variation within RQ values estimated by the approaches requires further investigation as it does not promote the level of confidence required by the user. Furthermore, this work adds to the recommendations made elsewhere [2] that there is a clear need to better share knowledge on the parameterisation of radionuclide transfer to biota and to provide authoritative collations of those data which are available.…”
Section: Variation In Estimated Rq Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation and comparison of the radioecological and dosimetry components of various approaches are required and this has begun through the Biota Working Group of the IAEA's EMRAS programme [4]. It is also important that approaches used are practicable, credible to stakeholders and fit for purpose [5].…”
Section: Introductionmentioning
confidence: 99%
“…Model intercomparison exercises have identified radionuclide transfer predictions as the greatest source of uncertainty in biota dose assessments [1,2]. In response to this an International Atomic Energy Agency (IAEA) Working Group was established to develop an international database of transfer parameters for wildlife [3].…”
Section: Introductionmentioning
confidence: 99%